KEMISKINAN MULTIDIMENSI PADA ANAK - - Ambariyanto (Trunojoyo University of Madura, 2013)
Children's poverty is urgently required solved problem for the development. Thus, this research paper aimed to identify the children's poverty based on non-moneter approach; it refers to the multidimentional poverty. However, the impact of non-poverty policy assessment is measured by monetary approach. Besides, the discussion has been yielded that the poverty approach with the use of multidimensional approach has been depicted the real life of children's condition whose have lack of education, health and living standard. Again, the impact on the assesment has shown the goverment intervention on the children's welfares were still become minor policy. Finally, this paper has conclude that poverty measurement approach must be actively responsive to the children's need on their welfare. In the long run, the policy focusing on children is very important, this because they are become an important determinant on the long term development.